SPIRITUAL MOTIVATION AND INSTITUTIONAL SUPPORT: IMPACT ON VOLUNTEER TEACHER EFFICACY IN JAMBI’S BOARDING SCHOOL - Mawardi Mawardi; Agil Munawar; Elza Eka Putri; Hambali Hambali; Habibah Binti Ayob; Mona Novita (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study aimed to investigate the influence of spiritual motivation and institutional support on teaching efficacy among volunteer teachers in boarding school. A cross-sectional survey design was employed, involving 218 volunteer teachers from 24 boarding school. Data were collected using adapted instruments measuring spiritual motivation, perceived institutional support, basic psychological needs satisfaction (autonomy, competence, relatedness), and teaching efficacy. Structural equation modeling (SEM) with partial least squares (PLS-SEM) was used for data analysis. The results revealed that spiritual motivation significantly and positively influenced teaching efficacy (β = 0.39, p < 0.001), both directly and through the mediation of satisfaction of basic psychological needs. Institutional support also exerted a significant positive effect on teaching efficacy (β = 0.31, p < 0.001), primarily mediated by the satisfaction of competence and relatedness needs. The interaction between spiritual motivation and institutional support produced a synergistic effect that enhanced the fulfillment of all three basic psychological needs. These findings extended SDT by demonstrating that spiritually grounded intrinsic motivation, when coupled with structured institutional support, creates an optimal motivational ecology for volunteer teachers in faith-based educational settings.